INVESTMENT IN TEXTILES ACTIVITIES INNOVATIVE OF THE ECONOMY IN EGYPTIAN REGIONAL PROJECTS - ELNASHAR, Elsayed A.; LIUBOKHYNETS, Larysa; TANASIIENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Today, the textile and clothing industry counts 143,000 companies, mostly SMEs, employing 1.3 million people (5% of EU manufacturing employment) generating a turnover of EUR 147 billion (3% of EU manufacturing value added) widely spread across the EU. However, a substantial portion of (mostly lower added value) textiles and clothing consumed in the EU is produced elsewhere in the world, often in Egypt in north Africa, Asia, taking advantage of very low labour costs. Disadvantages of this model include long-distance vulnerable supply chains, poor working conditions in "sweat-shops", and high environmental costs. We in Egypt are striving forward to be partnership is co-developed by member EU regions with an active participation in textile industry, involving the full quadruple helix of players, so to better connect regional authorities with industrial interests and needs. We in Egypt are striving forward the partnership employed a values add chain (innovations) approach along related priority domains of smart specialisation in member regions with the aim to create an investment pipeline of mature projects relying on new cross-sectoral industrial value chains developed by multiple stakeholders, so to achieve lasting improvements, in areas like: values add chain (innovations) in advanced manufacturing technologies for cleaner, less labour, resource intensive and circular production systems. The aim of the thematic platforms is to foster inter-regional collaboration around smart specialisation priorities and modernisation along global values add (innovations) chains.
Keywords: Investment; Textiles Activities; Innovative; Economy; Regional Projects